Institutional film and social public policies in Portugal during the late authoritarian regime (1957–1969) - Vidal, F.; Veloso, L. (Film History, 2024)
The aim of this article is to contribute to a better understanding of the complex, diffuse, and negotiated relationship between the use of cinema and Portuguese government practices during the authoritarian regime in Portugal. The study focuses on the engagement of the Junta de Acção Social (JAS, Social Action Committee), a Portuguese public body. It was created in 1956 to implement the Corporatist and Social Training Plan that produced, bought, and distributed institutional films about work and education. The article analyzes the national and transnational conditions of the development of a type of governmentality regarding social public policies, molded by the organization of the field of institutional films, and the comprehensive dissemination of the film industry in Portuguese society.